Answer:
Step 2: (z+3)=20/2
Explanation:
Given Eliza's Work:
![(z + 3)^2$ - 2 = 18\\Step 1:(z + 3)^2= 20\\$Step 2:\\Step 3: z + 3 = 10\\Step 4: z = -13 or z = 7](https://img.qammunity.org/2021/formulas/mathematics/high-school/q85tja0k7dowjxztvftwf0q8sveulg162z.png)
For Eliza to have obtained z+3 = 10 in step 3, she erroneously divided the right hand side of step 1 by 2. Therefore, what she wrote in her step 2
Step 2: (z+3)=20/2
However, the correct solution is:
![(z + 3)^2$ - 2 = 18\\Step 1:(z + 3)^2= 20\\$Step 2:√((z + 3)^2) =\pm √(20) \\$Step 3: z + 3 = \pm 2√(5) \\$Step 4: z = -3+ 2√(5)$ or z = -3 - 2√(5)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ezb5fk0tcsqbpu8ugnueqi4c5slmruita9.png)